MAIT cells are licensed through granzyme exchange to kill bacterially sensitized targets. - Kurioka, A; Ussher, J; Cosgrove, C; Clough, C; Fergusson, JR; Smith, K; Kang, Y; Walker, L; Hansen, T; Willberg, C; Klenerman, P (Nature Publishing Group, 2015)
Mucosal-associated invariant T (MAIT) cells are an innate-like T-cell population restricted by the non-polymorphic, major histocompatibility complex class I-related protein 1, MR1. MAIT cells are activated by a broad range of bacteria through detection of riboflavin metabolites bound by MR1, but their direct cytolytic capacity upon recognition of cognate target cells remains unclear. We show that resting human MAIT cells are uniquely characterized by a lack of granzyme (Gr) B and low perforin expression, key granule proteins required for efficient cytotoxic activity, but high levels of expression of GrA and GrK. Bacterial activation of MAIT cells rapidly induced GrB and perforin, licensing these cells to kill their cognate target cells. Using a novel flow cytometry-based killing assay, we show that licensed MAIT cells, but not ex vivo MAIT cells from the same donors, can efficiently kill Escherichia coli-exposed B-cell lines in an MR1- and degranulation-dependent manner. Finally, we show that MAIT cells are highly proliferative in response to antigenic and cytokine stimulation, maintaining high expression of GrB, perforin, and GrA, but reduced expression of GrK following antigenic proliferation. The tightly regulated cytolytic capacity of MAIT cells may have an important role in the control of intracellular bacterial infections, such as Mycobacterium tuberculosis.